Analisis Faktor Penurunan Jumlah Siswa Pada Sekolah-sekolah Kristen-Katolik di Kabupaten-Kota Magelang - Hariyani, Lily; Mulyono, Rahmat (Media Manajemen Pendidikan, 2025)
The significant decline in student enrollment at private schools, particularly Christian-Catholic schools in Magelang City and Regency, serves as the background of this study. The purpose of the research is to identify the factors contributing to the decrease in student numbers, examine the efforts made to sustain school operations, and explore the involvement of alumni, parents, and the church in addressing the issue. This study employs a qualitative approach, utilizing interviews, observations, and document analysis as data collection techniques. Data were gathered from five Christian-Catholic schools and analyzed using the Miles and Huberman interactive model, encompassing data reduction, data display, conclusion drawing, and verification. The findings reveal two main factors behind the decline in student enrollment: internal and external factors, both of which interact without one being dominantly influential. Various efforts have been undertaken to prevent further decline, including strengthening school management by principals and enhancing the active involvement of alumni, parents, and the church. The synergy among these stakeholders is crucial in ensuring the schools' sustainability amid ongoing demographic and social challenges.